Pupillographic Sleepiness Test and Polysomnography in Nondemented Patients with Ischemic White Matter Lesions. (24th November 2015) - Landwehr, Ralf; Liszka, Robert
Abstract : Background . Patients with ischemic white matter lesions (WML) frequently report nonrestorative sleep or daytime sleepiness. However, subjective estimations of sleep and sleepiness can differ considerably from objective measures. The pupillographic sleepiness test (PST) could identify patients with sleep disorders requiring polysomnography (PSG) and further treatment. Methods . We performed a PST and a PSG of 35 nondemented patients with WML, who reported nonrestorative sleep or daytime sleepiness, and assessed the diagnostic value of the pupillary unrest index (PUI). Sleep parameters were compared to normative data. Results . The mean PUI of WML patients was normal (5.89 mm/min) and comparable to PUIs of patients with other neurological disorders. All 9 of the 35 WML patients (25.7%) who had a PUI above normal also had clinically relevant sleep disorders (5: sleep apnea, 7: periodic leg movements, and 4: insomnia). Six patients with a normal PUI had mild to moderate primary insomnia. Conclusion . PST and PSG parameters were physiological in most patients with WML. Age-related changes and affective and neuropsychological disorders might account for their sleep-related complaints. An elevated PUI in patients with WML seems to indicate comorbid sleep disorders that require further diagnostic evaluation and treatment (sleep apnea, insomnia with periodic leg movements, but not primary insomnia).